2013
DOI: 10.1074/jbc.m113.460691
|View full text |Cite
|
Sign up to set email alerts
|

The Upf Factor Complex Interacts with Aberrant Products Derived from mRNAs Containing a Premature Termination Codon and Facilitates Their Proteasomal Degradation

Abstract: Background: Up-frameshift (Upf) factors eliminate aberrant mRNAs that contain a premature termination codon (PTC). Results: The Upf complex was recruited to a PTC product and promoted the degradation of a model unfolded protein. Conclusion:Upf factors facilitate the ubiquitin-dependent degradation of products derived from mRNA containing specific PTCs. Significance: The findings reveal a mechanism of quality control that prevents the production of aberrant products derived from mRNAs containing specific PTCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Notably, we also demonstrated that truncated SERPINB7 protein from the mutant r.796c>u transcripts is degraded by the 26S proteasome. In yeast, mRNAs harboring a faux 3 0 UTR stimulate Upf1-dependent proteasome-mediated degradation of the PTC products (Kuroha et al, 2009;Kuroha et al, 2013;Sugiyama et al, 2017). These findings collectively indicate that mRNA and protein stability might be regulated by the aberrantly long 3 0 UTR of mutant transcripts in humans.…”
Section: Discussionmentioning
confidence: 85%
“…Notably, we also demonstrated that truncated SERPINB7 protein from the mutant r.796c>u transcripts is degraded by the 26S proteasome. In yeast, mRNAs harboring a faux 3 0 UTR stimulate Upf1-dependent proteasome-mediated degradation of the PTC products (Kuroha et al, 2009;Kuroha et al, 2013;Sugiyama et al, 2017). These findings collectively indicate that mRNA and protein stability might be regulated by the aberrantly long 3 0 UTR of mutant transcripts in humans.…”
Section: Discussionmentioning
confidence: 85%
“…For example, UPF1’s E3 activity may contribute to the degradation of abnormal and potentially deleterious peptides encoded by NMD substrates. Previous studies in yeast found that peptides encoded by reporter NMD substrates were degraded by the proteasome, and that Upf1 was important for this process (Kuroha et al, 2013; 2009; Verma et al, 2013). However, the method by which Upf1 promoted selective degradation of such peptides was not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Some encode full-length proteins while others have truncated ORFs 49, 78,86 . Structural and biochemical evidence suggest that UPF1 has ubiquitin-ligase activity 99,100 , which may stimulate the proteasome to degrade aberrant proteins encoded by PTC-containing mRNAs 101,102 . The data supporting such NMD-associated protein degradation is limited to a few model substrates in S. cerevisiae and it appears that UPF1-stimulated acceleration of degradation only occurs for proteins that are inherently unstable 101,102 .…”
Section: Effects Of Nmd On Gene Expressionmentioning
confidence: 99%